U-4: THE CULTURAL, HISTORICAL AND POLITICAL STUDY OF KHUSHWANT SINGH'S NOVEL DELHI” : خشونت سنگھ کے ناول "دِلی" کا تہذیبی، تاریخی اور سیاسی مطالعہ - Qazi, Rashida; Ali, Muhammad; Shah, Imran Raza (International Journal of Islamic Business, Administration and Social Sciences (JIBAS), 2022)
The overall situation of civilization must be kept in mind in order to understand their characteristic; which means all those beliefs, values, thoughts, tactics, aspirations, etiquettes, habits, music and several other aspects which are prevalent or popular in the particular region. In this regard, Delhi is not a town like other minor cities. According to great historians and scholars, Delhi which was settled before Christ, has been abolished and retained seven times. According to recent observations and facts, the curt Delhi is eighth. The purpose of monograph (Research paper) is to show the status of Khushwant Singh as a historian. The novel Delhi was the result of his twenty years of experience (practice). Thus, he wrote a short history of Delhi discussing its different civilizations, cultures and political aspects. Khushwant singh has summed up this history of centuries in his novel “Delhi”. He has described the account of Delhi from its early era to current time (Up to killing of Indira Gandhi).The protagonist of this novel is bhag-mati (who is a transgender) has been presented symbolically. The way he is exploited by men and women, as he is not able to have a child; the same is the case with Delhi. Khushwant singh has aesthetically highlighted the ruins and bruises of Delhi in the historical context. Moreover, he has also focused and explained cultural, social, and civilized aspects of Delhi.